Optimasi Sodium Croscarmellose dan Pati Jagung Pregelatinasi dalam Orally Disintegrating Tablet Setirizin Dihidroklorida - Irawan, Eka Deddy; Sari, Lusia Oktora Ruma Kumala; Cahyaningrum, Nitta (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2022)
Abstract: Cetirizine dihydrochloride (Cetirizine diHCL) is an effective antihistamine to treat allergies. Cetirizin diHCL tablets are a dosage form that is commonly on the market. However, people who experience allergies will have symptoms of difficulty swallowing which make it difficult to take cetirizine diHCl tablets. Therefore, it is necessary to make cetirizine diHCl in the form of orally disintegrating tablets (ODT) which can dissolve in saliva in a few seconds without chewing tablets or drink water. The proportion of binder and super disintegran was used in ODT preparations must be taken into calculation because it will greatly affect the physical characteristics of the tablets. This study aims to optimize the super disintegran Croscarmelose Sodium and pregelatinasi corn starch binders using factorial design methods. The responses studied were flow rate, hardness, brittleness, wetting time, and disintegration time. The increased Croscarmelose Sodium factor reduces the flow rate and hardness, increases brittleness, and decreases wetting and disintegration times. The increased factor of pregelatinasi corn starch will increase the flow rate and hardness, reduce friability and increase wetting time and disintegration time. The optimum formula was obtained from the concentration of Croscarmelose Sodium 6.613 mg and pregelatinasi corn starch 20 mg which resulted in a flow rate response of 13.438 g/second, hardness 4.646 kg, friability 0.815%, wetting time 63.667 seconds, and disintegration time 18.641seconds.